2(2+4)2+4x=x(3+3)+2

Simple and best practice solution for 2(2+4)2+4x=x(3+3)+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2+4)2+4x=x(3+3)+2 equation:



2(2+4)2+4x=x(3+3)+2
We move all terms to the left:
2(2+4)2+4x-(x(3+3)+2)=0
We add all the numbers together, and all the variables
4x-(x6+2)+262=0
We get rid of parentheses
4x-x6-2+262=0
We add all the numbers together, and all the variables
-1x^6+4x+260=0
We do not support expression: x^6

See similar equations:

| 3a+11=7a+13 | | 3x^2+5x-6=7x-1 | | 7x-4(x+1)=2 | | -7+x/6=1 | | 2.25g-4.5=3g+6 | | 680=-8(-11x+3) | | t-4.25=-5 | | 38.7-3w=1.2 | | 7(-8-6x)=322 | | 5.4b+1=7.4b-5 | | g+6=-8 | | -16x^2+11x+85=0 | | 0.99x=1.29x | | g+3.5=10 | | 17n=−4 | | -17-2n=7(2n-7) | | F(x)=-2/3x+3 | | 3h/10-17=5.675 | | 35/d=7/2 | | 12+m-4+6=-2m+2 | | 5(a+2)=200 | | -6v+16=-2(v-6) | | 216=1/3(36)h | | 7+6*x=4^2+x^2 | | 6x-(-4(x+1))=2x+4 | | x/12+5/9=11/36 | | 8=-18+3/8(16-40m) | | 14(z-3)=2-3z | | -17x-1-10x+17=32x+1 | | 15x-15-7x+63=4x | | -4(n+1)+15n=0 | | 40/24=20/a |

Equations solver categories